Influences of narcissism and parental mediation on adolescents' textual and visual personal information disclosure in Facebook - Liu, Cong (2016)
This study aims to examine how adolescents' textual and visual personal information disclosure is influenced by their narcissistic personality and parental mediation. The moderation effect of parental mediation on narcissism was also explored. A total of 780 secondary school students aged between 13 and 18 participated in the study. Multiple regression analysis was conducted and results showed that narcissism increases the disclosure of both textual information and visual information while parental mediation decreases the disclosure of both textual information and visual information. Parental mediation moderates the link between narcissism and visual information disclosure, but not the link between narcissism and textual information disclosure. Implications of the findings for parents, school teachers, and educators were discussed.